Edge of desire : recent art in India - Asia Society - Museum; Art Gallery of Western Australia (2006)
[Dt.:] In der Ausstellung "Edge of Desire" sind ausgewählte Kunstwerke aus dem zeitgenössischen Indien gezeigt worden. Sie ist gemeinsam von der Asia Society und der Art Gallery of Western Australia ausgerichtet worden. Ein Teil der Exponate, die in den 1990er bzw. bis 2004 entstanden sind, ist als Online-Ausstellung weiterhin frei zugänglich. In den Bildern spiegelt sich der soziale und wirtschaftliche Wandel in Indien nach 1991 wieder. Zudem steht ein Vorwort der Ausstellungsmacher online zur Verfügung. - [Engl.:] The exhibition 'Edge of Desire: Recent Art in India' focuses on contemporary Indian art of the past decade, a period marked by enormous social, cultural, and economic change that counted political violence and rapid economic growth brought about by liberalization and foreign investment among the most significant. These issues and others form the context for the works of the thirty-eight artists in this exhibition, co-organized by the Asia Society and the Art Gallery of Western Australia. In the online-exhibition some of the exhibits are also available. The internet resource contains also a foreword by the exhibition's creator and a introduction.